Processing of the pulse signals during thickness measurement of biological tissues and non-destructive testing - Батраков, Д. О. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 2017)
A method for normalizing scattered by plane layered media signals with further processing according to prior developed algorithms to improve accuracy is proposed. The main idea of the method consists in the restoration of physical and geometrical parameters of the plane layered stratified medium. As a result, on the basis of computational experiments, was proved efficiency and effectiveness of the proposed method. Also discussed the possible ways of practical application of the proposed method in the treatment of road pavements sensing data with GPR "Odyag-1. Using the optional calibration procedure according to the data obtained by coring, also increases the reliability and accuracy of the assessment of the current state of road pavements